2006
DOI: 10.1590/s0036-46652006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of hepatitis C virus genotypes among blood donors from mid-west region of Brazil

Abstract: SUMMARYIn order to investigate the hepatitis C virus (HCV) genotypes in mid-west region of Brazil, 250 anti-HCV positive blood donors were studied. Among them, the anti-HCV serological status was confirmed in 205 (82%). HCV RNA was detected in 165 samples, which were genotyped. HCV types 1, 2 and 3 were found in 67.9%, 3% and 29.1% of the donors, respectively. In Goiás state, subtype 1a (50%) was the most prevalent, followed by subtypes 3a (30.9%) and 1b (16.7%). In Mato Grosso state, subtype 1a was also predo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
16
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 13 publications
6
16
1
4
Order By: Relevance
“…The genotype of the other nine samples could not be determined due to insufficient material. These data were similar to those previously found in Brazil, where genotype 1 is predominant (1,4,26,31,36). These data are in contrast to the genotype distribution observed by Busek et al (8) in a study conducted among ten patients from a haemodialysis centre, where there was a higher prevalence of genotype 3 followed by genotypes 1 and 2.…”
Section: Discussionsupporting
confidence: 90%
“…The genotype of the other nine samples could not be determined due to insufficient material. These data were similar to those previously found in Brazil, where genotype 1 is predominant (1,4,26,31,36). These data are in contrast to the genotype distribution observed by Busek et al (8) in a study conducted among ten patients from a haemodialysis centre, where there was a higher prevalence of genotype 3 followed by genotypes 1 and 2.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, another study conducted in male prisoners from the same penitentiary complex found genotype 1 in 80% of the samples (1a = 60%), followed by genotype 3a (13.3%) 28. In this sense, the HCV genotypes circulating in Goiás prisoners reflect the diversity of this virus in Goiás, Central Brazil 29,30 .…”
Section: Methodsmentioning
confidence: 99%
“…In Brazil, several studies have been conducted to determine the distribution of HCV genotypes among different groups of individuals. Most of these studies have shown a predominance of genotype 1 (Krug et al 1996, Oliveira et al 1999, Paraná et al 2000, Busek & Oliveira 2002, Codes et al 2003, Vogler et al 2004, Martins et al 2006, Silva et al 2006. The aim of the present study was to determine with precision the frequency of each HCV genotype in the South of Brazil, by studying a large cohort of patients from Rio Grande do Sul (RS) and Santa Catarina (SC), the southernmost states of the country.…”
mentioning
confidence: 93%